Textile Effluent Treatment Plant Sludge: Characterization and Utilization in Building Materials - Rahman, Md. Mostafizur; Khan, Maksudur R.; Uddin, Md. Tamez; Islam, Akhtarul (Springer, 2016)
The main objective of this study is to characterize and find a potential use of textile effluent treatment plant (ETP) sludge produced in Bangladesh. Textile ETP sludge collected from the local textile industries have been characterized in the laboratory. The physicochemical and engineering properties of the sludge have been studied. Collected ETP sludge has been processed to get cement-like fine powder that has been used for partial replacement of Portland cement/sand in the composition of the mortar and concrete specimens. Different mechanical (compressive and flexural strength), physical (water absorption) and morphological (porosity) properties of the test specimens have been evaluated. The test result shows that the addition of sludge in the mortar and concrete composition as a substitution of Portland cement or sand decreases the compressive strength and flexural strength, and increases the water absorption and porosity of the mortar and concrete specimens. Leaching study, conducted for the sludge-based mortar and concrete specimens following tank leaching test procedure, reveals that the concentration of leached metals is quite low than the limits specified by the Department of Environment in Bangladesh. These results amply demonstrate that textile ETP sludge can be utilized for making non-structural building components where lower strength is justified.